Adoption of the “Enova Santé” Hospital Information System by Head Nurses in Souss Massa, Morocco - Adam Abassi; Elhabib Moukrim; Ayoub Oulamine (Asia Pacific Journal of Health Management)
The integration of information technologies in the healthcare sector aims to enhance the quality of care, service efficiency, and clinical data management. Within this framework, hospitals in the Souss Massa region (Morocco) have deployed the hospital information system “ENOVA Santé”. Although the perceived benefits of this system are recognized, its adoption remains closely linked to the users’ involvement, particularly head nurses, whose role is essential in the deployment, appropriation, and dissemination of this technology within the nursing community. The present study examines the factors influencing the adoption of the “ENOVA Santé” by head nurses in hospitals in the Souss Massa region (Morocco).